COBIT 5 PENERAPAN TATA KELOLA TEKNOLOGI INFORMASI PADA EVENT TAHUNAN PRODI SISTEM INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 DENGAN DOMAIN ALIGN PLAN ORGANIZE (APO) 07 - Angga Galant Bil Hikma; Muhammad Ridho Fardani (Aisyah Journal Of Informatics and Electrical Engineering, 2021)
ABSTRACT The implementation of information technology governance at the annual event of the UISI information system study program does not have policy documents and procedures according to the COBIT 5 APO 07 standard.The results of the research show that the literature study obtained values from APO 07 is Making procurement and staff maintenance policy documents, Making documents Procedures for selecting key personalities (Division Coordinator), Making evaluation activities in each division and providing target scores or time on assignments given to committee members, Making policy documents about the number of human resources and assignments to be assigned, and Making event activity procedures documents , starting from the beginning to the end of the event, and making evaluation documents that can be used as a reference for the development of these organizational events in staff or human resource management. Keywords: Government, Cobit 5, APO 07, Evaluation ABSTRAK Penerapan tata kelola tenkonolgi informasi pada event tahunan prodi system informasi UISI tidak memiliki dokumen kebijakan dan prosedur sesuai standar COBIT 5 APO 07. Hasil penelitian menunjukan bahwa studi kepustakaan yang didapatkan nilai – nilai dari APO 07 ialah Membuat dokumen kebijakan pengadaan dan perawatan staff, Membuat dokumen prosedur tentang penyeleksian personal kunci (Koordinator Divisi), Membuat kegiatan evaluasi pada setiap divisi dan memberikan target nilai ataupun waktu pada tugas yang diberikan pada anggota panitia, Membuat dokumen kebijakan tentang jumlah sumber daya manusia dan tugas yang akan diberikan, dan Membuat dokumen prosedur kegiatan event, dimulai dari awal hingga akhir event selesai serta membuat dokumen evaluasi yang bisa menjadi acuan untuk berkembangnya event organisasi tersebut dalam pengelolaan staff atau sumber daya manusia. Kata Kunci: Tata Kelola, Cobit 5, APO 07, Kerangka Kerja, IT Blueprint